Peran Promosi Digital Dalam Membentuk Preferensi Konsumen Pendidikan - Abdurrahman Al Labib; Nurfuadi . (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the role of digital promotion in shaping consumer preferences in the education sector. The development of information technology and the internet has transformed consumer behavior in seeking information and making decisions, including in choosing educational institutions. Digital promotion through various platforms such as social media, websites, search engines, and digital advertising (Google Ads, Facebook Ads, Instagram Ads, LinkedIn Ads, Twitter Ads, and TikTok Ads) has become a strategic instrument in building institutional image, increasing awareness, and influencing prospective students’ perceptions and attitudes. This research employs a descriptive qualitative approach through literature review to examine the concepts, strategies, and implementation of digital promotion in educational services. The findings indicate that promotion intensity, message relevance, quality of visual content, accurate targeting, and data-driven evaluation significantly contribute to the process of shaping consumer preferences in education. Consistent, interactive, and credible information exposure through digital media strengthens positive perceptions and increases the likelihood of selecting a particular institution. Therefore, digital promotion functions not only as a marketing communication tool but also as a strategic factor in influencing consumer preferences and decision-making in the education sector.